Insights into the experiences of older workers and change: through the lens of selection, optimization, and compensation. - Unson, Christine; Richardson, Margaret (The Gerontologist, 2013)
Purpose: The study examined the barriers faced, the goals selected, and the optimization and compensation strategies of older workers in relation to career change. Method: Thirty open-ended interviews, 12 in the United States and 18 in New Zealand, were conducted, recorded, transcribed verbatim, and analyzed for themes. Results: Barriers to finding and maintaining work included task difficulty, problems with coworkers and management, lack of self-confidence, health/physical limitations, ageism, and stereotyping. Respondents' most frequently selected goals for a new career were the desire to help others, work satisfaction, and acquisition of learning. Seventy-five percent of respondents in paid employment had earning an income as a goal. Optimization strategies included drawing on past experience, assessing skills, seeking careers/organizations that fitted their values, and a willingness to accept lower pay or unpaid work. Attitudinal strategies included focus and persistence, optimism, and positive attitudes toward change. The compensation strategies reported were on-the-job training; help from coworkers, clients, or customers; friends and family social support; and professional networks. Management practices considered helpful were flexible work schedules, supervisors' patience, and formal recognition of the value of older workers. Conclusion: This qualitative study, using the SOC framework, showed that evaluating one's skills and values, being positive about change, and being part of a supportive work environment were key contributors to adaptive competence. © 2012 © The Author 2012. Published by Oxford University Press on behalf of The Gerontological Society of America. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com.
Keywords: *Aging/px [Psychology]; *Compensation and Redress; *Employment/px [Psychology]; *Goals; *Self Concept; Aged; Aged, 80 and over; Aging; Compensation and Redress; Employment; Encore careers; Female; Goals; Humans; Inservice Training; Interviews as Topic; Male; Middle Aged; Models, Psychological; Motivation; Multivariate Analysis; New Zealand; Qualitative Research; SOC; Self Concept; Social Support; United States; Workplace; aged; aging; article; compensation; dept.pch; employment; female; human; in service training; interview; male; middle aged; motivation; multivariate analysis; peer-reviewed; psychological aspect; psychological model; qualitative research; self concept; social support; very elderly; workplace

Predictors of success for community-driven water quality management—Lessons from three catchments in New Zealand - Tyson, Ben; Unson, Christine; Edgar, Nick (Applied Environmental Education & Communication, 2017)
Three community engagement projects on the South Island of New Zealand are enacting education and communication initiatives to improve the uptake of best management practices on farms regarding nutrient management for improving water quality. Understanding the enablers and barriers to effective community-based catchment management is fundamental to planning, implementing and evaluating these initiatives. This article investigates some key predictors of success or determinants of effective community engagement. Six factors were identified: access to science, training, and information; confidence in regulatory policies; leadership; farm planning and monitoring; trust in the public; and concern for water quality. © 2017 Taylor & Francis Group, LLC.
Keywords: dept.pch

Racial and Ethnic Disparities in Chronic Stress among Male Caregivers - Unson, Christine; Njoku, Anuli; Bernard, Stanley; Agbalenyo, Martin (International Journal of Environmental Research and Public Health, 2023)
Whereas research on caregiving is well documented, less is known about gender inequalities in caregiver stress, coping mechanisms, and health outcomes, all of which may vary by race, ethnicity, and socioeconomic status. This scoping review investigated racial and ethnic disparities using the Stress Process Model among male caregivers. Several databases were searched including Academic Search Premier, Medline Complete, APA PsycInfo, CINHAL, Google, ProQuest, and Web of Science. Included were peer-reviewed articles in English, published from 1990 to 2022. A total of nine articles fulfilled inclusion criteria. Most of the articles indicated that compared to White male caregivers, African American male caregivers provided more hours of care, assisted with more activities of daily living (ADLs) and instrumental activities of daily living (IADLs), and experienced more financial stress. In terms of coping style, one study found African American male caregivers, compared to White male caregivers, held negative religious beliefs. Another study showed that they were at a higher risk for stroke than their White counterparts. The search revealed a dearth of studies on racial disparities in stress, coping, and health outcomes among male caregivers. Further research is needed on the experiences and perspectives of male minority caregivers. © 2023 by the authors.
Keywords: African American males; aging; caregiver burden; caregiving; coping; dept.pch; health and aging; health disparities; intersectionality; male caregiver; masculinity; older adults; peer-reviewed

Uncertainty in transitions of African American caregivers - Unson, Christine; Flynn, Deborah; Chukwurah, Queendalene; Glendon, Maryann; Testut, Tammy (Issues in Mental Health Nursing, 2020)
The purpose of this study was to gain an understanding of the ambiguities and uncertainties experienced by a diverse group of African-American caregivers. The study applied Schlossberg's transition theory (TT) and Mishel’s revised uncertainty theory to narratives of self-identified African-American caregivers who provided care at least 5 h a week. The men (6) and women (8) were mostly unmarried, mostly caring for a parent or grandparent. The caregivers’ average age was 52 (SD = 19; ages ranged from 24 to 82 years); and the care recipients’ average age was 84 (SD = 9). Six care recipients had dementia and the remainder had multiple disease diagnoses. Narratives were obtained by in-depth interviews or focus group discussions. These were audio-recorded, transcribed verbatim professionally and analyzed independently by trained coders. Schlossberg’s TT contextualized whereas Mishel’s RUIT illuminated the characteristics of the transition, its associated uncertainty, and their relationship to the development of caregiver stress. Situational factors such as difficulties with illness symptoms of the care recipient, conflict between previous experience and current expectations and the adjustments to the new caregiving role, burdened younger caregivers more than older caregivers. Self-factors related to lack of knowledge about the illness and feelings of lack of control. Social support was predominantly provided by family members, and its absence resulted in conflict among siblings and caregiver stress. The most common coping strategies include religiosity, expectations of reciprocity, and coming to terms with the uncertainty. Understanding the feelings, perceptions and needs of caregivers in transition is tantamount to providing nursing care.
Keywords: Adaptation, Psychological; Adult; African American; African Americans; Aged; Aged, 80 and over; Caregivers; Female; Grandparents; Humans; Male; Middle Aged; Narration; Parents; Social Support; Stress, Psychological; Uncertainty; Young Adult; adult; aged; caregiver; child parent relation; coping behavior; dept.nur; dept.pch; female; grandparent; human; male; mental stress; middle aged; peer-reviewed; psychology; social support; uncertainty; verbal communication; very elderly; young adult

Strategies for living long and healthy lives: Perspectives of older African/Caribbean-American women - Unson, Christine G.; Trella, Patricia M.; Chowdhury, Sutopa; Davis, Elizabeth M. (Journal of Applied Communication Research, 2008)
The influence of health and socioeconomic status on perceptions of aging and adaptation strategies of older African/Caribbean-American women was examined. Responses of 38 women (average age = 77.3 years) to: “What do you like and dislike about growing old?” and To what would you attribute your long life? were analyzed. Respondents were classified as: financially independent/healthy, financially dependent/healthy, financially independent/not healthy and financially dependent/not healthy. Narratives revealed declining health and restricted financial resources limited perceptions of opportunities for well-being. Despite differences in health and financial status, groups had some common strategies: avoiding risk behaviors, holding moral beliefs, optimism, altruism and spirituality. It was concluded that health and socioeconomic status had some influence on perceptions of aging and adaptation strategies.
Keywords: African-American; Aging perspectives; Caribbean-American; Older adult; dept.pch

The Socialization of Unpaid Family Caregivers: A Scoping Review. - McAllum, Kirstie; Simpson, Mary; Unson, Christine; Fox, Stephanie; Kilpatrick, Kelley (Res Aging, 2021)
As unpaid family caregiving of older adults becomes increasingly prevalent, it is imperative to understand how family caregivers are socialized and how they understand the caregiving role. This PRISMA-ScR-based scoping review examines the published literature between 1995-2019 on the socialization of potential and current unpaid family caregivers of older adults. Of 4,599 publications identified, 47 were included. Three perspectives of socialization were identified: (1) role acculturation; (2) role negotiation and identification; and (3) specialized role learning. The findings show how socialization involves different contexts (e.g., cultures), imperatives for action (e.g., circumstances), socialization agents (e.g., family), processes (e.g., modeling), and internal (e.g., normalization) and external (e.g., identification) consequences for caregivers. Future research could fruitfully explore how caregivers manage key turning points within the socialization process, disengage from the caregiving role, and negotiate the socialization and individualization processes within diverse cultural and funding contexts., (C)2021Sage Publications
Keywords: Aged; Caregivers; Family; Humans; Socialization; aged; care behavior; caregiver; caregiving; cultural factor; dept.pch; elder care; family; funding; human; individualization; intergenerational support; learning; negotiation; peer-reviewed; review; socialization

Dementia and Caregiver Stress: An Application of the Reconceptualized Uncertainty in Illness Theory. - Unson, Christine; Flynn, Deborah; Glendon, Mary Ann; Haymes, Elayne; Sancho, Diane (Issues in mental health nursing, 2015)
The Reconceptualized Uncertainty in Illness Theory (RUIT) was used to investigate antecedents to, appraisals of, and ways of coping with stressful caregiving. Four focus groups with caregivers (8 males and 16 females) of relatives with dementia were conducted; 15 cared for their parents and the remainder cared for their spouses. They were recruited from an adult care center and other community settings in a metropolitan area in New England. The discussions were audiotaped and transcribed verbatim. Two researchers independently coded the transcripts. Thematic analysis was structured according to the RUIT. The study is unique in its application to caregivers as opposed to patients and to all of the elements of the RUIT. Caregivers experience uncertainty in similar ways to patients with life-altering illness. Symptom severity--lack of personal boundaries, repetitive and aggressive behaviors, and the need for constant care--was the most frequent source of stress. The appraisals were mostly negative and included feelings of resentment, a lack of support from family members, financial strains, and loss of freedom. Self-improvement and self-care were important aspects of coping. Spirituality and humor were other coping skills that respondents used. Not all respondents said they were coping and some also reported that support from health care providers was not always helpful. Nurses can help improve coping by explaining the factors that contribute to caregiver strain and uncertainty, and by assisting caregivers to anticipate the effects of the caregiving role.
Keywords: *Adaptation, Psychological; *Caregivers/px [Psychology]; *Dementia/px [Psychology]; *Stress, Psychological/pc [Prevention & Control]; *Uncertainty; Adaptation, Psychological; Adult; Aged; Aged, 80 and over; Caregivers; Dementia; Dementia/th [Therapy]; Female; Humans; Male; Middle Aged; Models, Psychological; Narration; Stress, Psychological; Stress, Psychological/et [Etiology]; Uncertainty; adaptive behavior; adult; aged; caregiver; dementia; dept.nur; dept.pch; etiology; female; human; male; mental stress; middle aged; peer-reviewed; prevention and control; psychological model; psychology; uncertainty; verbal communication; very elderly

Predictors of types of caregiver burden - Unson, Christine; Flynn, Deborah; Haymes, Elayne; Sancho, Diane; Glendon, Mary Ann (Social Work in Mental Health, 2016)
This study identified the types of caregiver stress and the caregiver and care management characteristics that are associated with this stress. 169 caregivers were recruited from a variety of community settings that cater to caregivers in a New England metropolitan area. They completed the Zarit Burden Interview (ZBI) and a questionnaire concerning their care recipient and caregiving arrangements. Principal Components Analysis on the ZBI resulted in five factors: personal strain/loss, uncertainty/inadequacy, social strain/embarrassment, anger, and dependency. The average age of the caregiver was 59.95 years (SD = 11.75) and the average age of the CR was 83.44 years (SD = 7.88). Of the 169 caregivers, 82% were women, 61.5% daughters/in-law or wives (12.9%), 34.3% were solo caregivers; 16.8% little or no burden, 39.9% reported mild to moderate burden, 35% moderate to severe burden, and 8.4% had severe burden. Dependency (22.4%) and personal strain/loss (13.7%) had the highest proportions reported as “often” to “nearly always.” The ZBI was predicted by only two caregiver characteristics, indicating that it is not sensitive to the experiences of different types of caregivers. Caregivers experience different types of burden depending on their gender, kinship roles, and levels of involvement in the care of their older relative. Solo caregiver status and age (younger) significantly predicted most if not all 5 burden types. Solo and young caregivers experienced the highest levels of caregiver burden. Social work practice must identify the caregiver’s life stage and other and self-expectations in relation to dependency, personal loss, embarrassment, anger, or uncertainty. © 2016 Taylor & Francis.
Keywords: Caregiver burden; United States; adult; aged; anger; caregiver burden; controlled study; dependency; dept.nur; dept.pch; expectation; female; gender; human; human experiment; interview; male; principal component analysis; questionnaire; recipient; social work practice; strain; uncertainty

It’s What We Do: Māori Carers Talk About Roles, Challenges, and Coordination in Caring for Older Family Members - Simpson, Mary; McAllum, Kirstie; Unson, Christine; Fox, Stéphanie; Hancock, Te Oha (Innovation in Aging, 2020)
As the population of Aotearoa/New Zealand heads towards one-in-four being aged over 65-years-and-over by 2040, it is anticipated that family members will play an increasingly important role in caring for older relatives with chronic and age-related health issues. Multi-generational, and in particular three-generational living arrangements, combined with family care of older relatives are a growing trend; a trend already even evident among Māori communities. This paper reports on a study that explored the care experiences and expectations of 14 past and current Māori carers (aged 23 to 72-years) of older relatives. Interviews were audio-recorded, transcribed verbatim, and coded independently. The initial thematic analysis revealed nine themes and participants were invited to feedback on the summary in person or in writing. The feedback resulted in the original themes being collapsed into four (with subthemes): “Care is Normal”; “Collective Coordination of Care”; “Insider-Carer—Outsider Perspectives on Caring”; and “Societal Influences on Family Care/Carers”. Firstly, these themes highlight how Māori cultural norms infuse direct care, support, and coordination roles within family care of the older family member. Secondly, they reveal the challenges for family carers in talking about their work with others, especially (thirdly) in the face of negative attitudes towards care and carers of an older family member within wider society. These findings have implications for cultural and wider socio-political influences in socialising different groups to carer role expectations. If society is to better prepare future caregivers for their role, ongoing research is needed with the various cultural groups in Aotearoa/New Zealand.
Keywords: dept.pch; peer-reviewed

Correlates of Strength and Balance Training Exercises in Older African American Adults. - Jiakponnah, Nwanyieze; Ngozi MD, MPH; Unson, Christine; Chukwurah, Queendaleen; Chinenye MD, MPH (Gerontologist, 2021)
Background and Objectives: This study investigated the behavioral and psychological correlates of strength and balance training (SBT) participation among older African Americans. Research Design and Methods: A cross-sectional survey of 90 older African Americans (M = 66.7 ± 8.7 years; 70% female) was conducted to assess correlates of intention to undertake SBT exercises and the number of days that they currently engage in SBT. The Theory of Planned Behavior (TPB) and the threat appraisal of the Protection Motivation Theory (PMT) were used as frameworks for the analyses. Results: The intention to do SBT exercises was positively associated with favorable attitudes and subjective norm, knowledge about the benefits of SBT, and hours worked per week. The frequency of SBT participation was significantly correlated with behavioral intention, high fear of falling, and a low score on the kinesiophobia scale. Discussion and Implications: This study demonstrated the utility of the TPB and PMT's threat appraisal construct in modeling intention and number of days of SBT participation among African American older adults. The study affirmed the link between intention and behavior and between knowledge of the benefits of SBT and intention. Fear of falling's positive association with days of SBT suggests that respondents' saw SBT's efficacy in reducing falls. The unique contributions of this study are the inclusions of kinesiophobia as a correlate and multiple threat appraisals in the PMT. Health promotion interventions should consider the interrelationship among these constructs. © 2021 The Author(s) 2021. Published by Oxford University Press on behalf of The Gerontological Society of America. All rights reserved.
Keywords: Accidental Falls; African American; African Americans; Aged; Attitude; Cross-Sectional Studies; Exercise; Fear; Fear of falling; Female; Humans; Intention; Kinesiophobia; Male; Psychological Theory; Subjective norm; Surveys and Questionnaires; Theory of Planned Behavior; adult; aged; article; behavior; controlled study; cross-sectional study; dept.pch; exercise; falling; fear; fear of falling; female; health promotion; human; male; motivation; peer-reviewed; prevention and control; psychological theory; questionnaire; theoretical study